LOCAL ECONOMIC DEVELOPMENT STRATEGY FOR REDUCING POVERTY IN SURALAGA EAST LOMBOK REGENCY (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
This study plans a local economic development strategy to create competitiveness to improve the community’s economy. The research method is qualitative with a case study approach. I identified the results of the discussion using a SWOT analysis. The results showed that the development of the local economy had a positive impact, namely that the development of the local economy created new jobs, increasing the economy of the surrounding community. Optimizing local human resources with regional development strategies potential, optimizing infrastructure, opening cooperation with other regions and using science and technology.